Barrett's esophagus: Analyses from human and experimental animal studies Barrett-Ösophagus: Erkenntnisse beim Menschen und aus experimentellen Tierstudien - Kushima, R.; Mukaisho, K. I.; Takemura, S.; Sugihara, H.; Hattori, T.; Vieth, M. (Pathologe, 2013)
Whereas attention in the past has been focused on goblet cells as the primary marker for Barrett's esophagus (BE), the recent change in the definition now includes the non-goblet cell columnar cell-lined esophagus. In the present study the histological features of neoplasia of the lower esophagus and esophago-gastric junction in a German cohort were examined using immunohistochemical staining for MUC, CD10, intestinal and gastric type major tight junction proteins (claudins). Experimental studies using rat duodenogastric content reflux models have also been performed and data show that most neoplastic lesions of the esophageal glands in humans express gastric mucin phenotypes. Cardiac type mucosa was the main histological type in the surrounding mucosa of neoplastic lesions; however, most cardiac type mucosa has intestinal type tight junction proteins. BE with goblet cells has been reported to originate from stem cells located in the basal layer of esophageal squamous cell epithelium in previous models. However, the cardiac type mucosa seems to develop from the site of the stomach and not from the basal layer of esophageal squamous cell epithelium according to our model. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Animal; Barrett; Development; Human; Neoplasia